Estimation of 2021 M7.3 Flores Sea Earthquake Displacement Derived from Static GNSS Observation - Putra Maulida; Yola Asis Herawati; Putra Rizkiya; Sari Rizky; Akbar Kurniawan; Safanata Azza Laksono; Yanto Budisusanto (Geoid, 2025)
On 12 December 2021, a Mw 7.3 strike-slip earthquake ruptured a previously unmapped fault in the Flores Sea, later identified as the Kalaotoa fault. The event damaged 345 buildings and displaced nearly 3,900 residents, highlighting the seismic hazard in the Sunda–Banda arc transition zone. In this study, we analyzed static GNSS data from the Indonesian Continuously Operating Reference System (InaCORS) to estimate coseismic displacements. Daily coordinate solutions, corrected for satellite orbit, ionospheric, and tropospheric errors, were processed to extract the coseismic offsets during the event. Results show horizontal displacements of up to 3.0 cm at CFLT, 2.2 cm at CMRE, and 1.9 cm at CUKA, with vertical motions reaching ~1.3 cm uplift at CUKA and ~0.9 cm subsidence at CMRE, which suggests that the earthquake not only incorporates the strike-slip movement but also the dipping movement. Stations near the epicenter moved northwestward, while northern stations moved southeastward, consistent with a right-lateral strike-slip mechanism. To validate the observations, we employed a half-space elastic dislocation model based on centroid moment tensor solutions for fault geometry. The model reproduced the general displacement patterns but showed systematic discrepancies, including overestimation of horizontal offsets by nearly a factor of two at near-epicenter stations (CFLT, CMRE, CUKA, CLWB) and underestimation of vertical motions by up to 2–3 cm. The misfit corresponds to an RMSE of ~1 cm for horizontal and ~3 cm for vertical displacement. These results indicate that a single homogeneous slip model oversimplifies the rupture, suggesting the need for more complex fault segmentation or slip inversion. Overall, this study demonstrates the capability of GNSS to capture coseismic deformation robustly and emphasizes its importance for refining earthquake source models and improving seismic hazard assessment in tectonically complex regions such as eastern Indonesia.